Functional State of the Liver in Rheumatoid Arthritis (Literature Review) - Khadjimatova I.X; Azimova M.M; Abzalova D.A (Zien Journals, 2023)
The article presents the state of the liver in patients with rheumatoid arthritis.
Keywords: Rheumatoid arthritis; biologically active substances; liver